Factors Influencing Malnutrition among Children under Five in Dikwa: An Analysis of Diet, Health, and Socioeconomic Conditions - Airaoje, Ojemeiri Karl; Falobi, Funmi; Uchendu, Chinelo Ebele; Akintayo, Atinuke Olubukade; Obada, Aruaye Afeye (Budapest International Research and Critics University, 2025)
Malnutrition is a broad term commonly used to describe deficiencies, excesses, or imbalances in a person’s intake of energy and nutrients required for proper growth and function. This study investigates the socio-economic, dietary, and environmental determinants of childhood malnutrition in a rural Nigerian community. The findings reveal that malnutrition is most prevalent among children aged 1–2 years (33.1%), coinciding with the critical “first 1,000 days” of development. A higher prevalence among female children (61.5%) suggests potential demographic or sampling influences. The data also show that 69.0% of caregivers engage in farming, with only 7.2% employed in the formal sector, linking income instability and food insecurity to poor nutritional outcomes. Access to healthcare is limited for 60.6% of the population, further compounding the issue. Dietary analysis indicates a heavy reliance on carbohydrate-rich staples (41.5%) and low intake of protein, fruits, and vegetables, raising concerns about micronutrient deficiencies. Educational disparities also emerged, with 46.9% of caregivers lacking formal education, affecting their ability to implement optimal feeding practices. Statistically significant associations were found between meal frequency and child weight status (χ²(2, N = 335) = 264.98, p < .001), maternal education and supplement provision, and access to clean drinking water and malnutrition status. The study recommends that caregivers should focus on the first one thousand days to enable the prioritization nutrition interventions from pregnancy to age two through breastfeeding promotion, timely complementary feeding, and regular growth monitoring.